FENOMENA CHILDFREE PADA PASANGAN MUDA DI DAERAH KOTA CIREBON DITINJAU BERDASARKAN HUKUM KELUARGA ISLAM - Asep Saepullah; Ahmad Rofi'i; Putri Berlian Sari (IAIN Syekh Nurjati Cirebon, 2023)
The childfree phenomenon has emerged on a global scale. The childfree phenomenon itself has existed since the 1500s in several countries such as France, England and the Netherlands. However, the term childfree appeared in Indonesia beginning with a statement by a public figure on his social media account, who declared himself an adherent of the childfree principle (married without having children). And along with the times, the human mindset also developed. Having children is not an obligation, rather a life choice and mutual agreement between husband and wife. This phenomenon is not only contrary to the noble values of the nation's culture, it becomes a little confusing when it occurs within the body of Muslims, bearing in mind that from a young age Muslims have been instilled with the understanding that marriage is a way to perfect religion and one of the missions marriage is to have godly offspring. This study aims to answer the questions that form the formulation of the problem: